Al-Ta‘līm al-Islāmī al-maftūḥ ladá KH. Sahal Mahfudz (1937-2014) - Irham Irham (Studia Islamika, 2022)
KH. Sahal Mahfudz represents Indonesia’s traditional ulama (salaf) with an open mind to change. His existence is crucial because he has held various highest positions in several leading Indonesian religious institutions, such as Chairman (Rais Aam) of the Nahdlatul Ulama Executive Board (PBNU) for three periods and as Chairman of the Indonesian Ulama Council (MUI) for 15 years. This article highlights his thoughts on integrating Islamic education with socio-cultural and scientific contexts. By examining his works, this article concludes that Islamic education, according to KH. Sahal Mahfudz has an integrative function with four main criteria. First, it has an integrated fundamental role. Second, it is not closed, not isolated from the socio-cultural context and has an accommodative attitude, and is open to revitalization. Third, it supports an interdisciplinary-multidisciplinary way of thinking. Fourth, it has an innovative character by bringing together tradition and modernity. From these findings, this article mentions these ideas as open Islamic education of KH. Sahal Mahfudz.